Analisis Penerapan PSAK 10 Pada Transaksi Ekspor dan Impor Pada Sektor Perdagangan - Tatsbita, Fishala Azka; Sudaryono; Sri Sapto Darmawati (ARBITRASE: Journal of Economics and Accounting, 2025)
This study aims to analyze the implementation of PSAK 10 regarding the Effect of Change in Foreign Exchange Rates on export and import transactions at PT Perushaan Perdagangan Indonesia (PPI) duting the 2020-2023 period, identify the challenges faced, and assess its impact on financial statements. The research employed a descriptive qualitative method using secondary data obtained from the company’s annual financial reports and relevant literature. Data collection techniques included documentation and literature review, while data analysis techniques applied were content analysis and descriptive qualitative analysis to evaluate the compliance of PSAK 10 implementation with foreign exchange fluctuations, accounting treatment of exchange differences, and financial statement disclosures. The results show that PT PPI has implemented PSAK 10 in accordance with the standard, using the Bank Indonesia middle rate at initial recognition and the closing rate at the end of the period for monetary items. The main challenges include determining the appropriate exchange rate, managing foreign exchange fluctuation risks, and ensuring consistent recording. Exchange rate fluctuations, particularly in USD and SGD, have a significant impact on asset values, liabilities, and profit or loss, where the appreciation of foreign currencies tends to increase export revenues but also raises import costs. The study concludes that the implementation of PSAK 10 at PT PPI has been carried out properly and in compliance with the standard, although more optimal foreign exchange risk management strategies are needed to minimize the adverse effects of currency fluctuations on financial performance.